Perbandingan Laju Aliran Massa Air Panas Terhadap Air Dingin yang Masuk Ruangan Pencampuran - Aloysius Eddy Liemena (ARIKA, 2011)
In course of hot water mixing and the cool water, we are given on how manay hot water and the cool water pouring into the mixing column of second. This research target is to determine tendency (fast trend) ratio of hot current with temperature 60 0C to accelerate the cool current with 10 0C of mixing column with temperature yelded gyrate from 45 0C till 25 0C. Benefit expected from this research is deepen theory thermodynamics and fluid mechanics and technique application and for the related / relevant technological science area especially with mixing column making (mixing chamber). Methodologies weared in this research is descriptive methodologies that is analyse a steady stream from hot water and the cool water entering an mixing column and which also yield warm water. From hot water mixing at temperature 60 0C with cool water at temperature 10 0C, yielding warm water with temperature which vary from 45 0C till temperature 25 0C yield fast ratio degradation of hot current to cool water with variation of, y from 2,34 till 0,43 (downhill).